2017
DOI: 10.1089/neu.2016.4721
|View full text |Cite
|
Sign up to set email alerts
|

Natural History of Headache Five Years after Traumatic Brain Injury

Abstract: Headache is one of the most frequently reported symptoms following traumatic brain injury (TBI). Little is known about how these headaches change over time. We describe the natural history of headache in individuals with moderate to severe TBI over 5 years after injury. A total of 316 patients were prospectively enrolled and followed at 3, 6, 12, and 60 months after injury. Individuals were 72% male, 73% white, and 55% injured in motor vehicle crashes, with an average age of 42. Pre-injury headache was reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
78
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(82 citation statements)
references
References 27 publications
3
78
0
1
Order By: Relevance
“…In fact, it was reported that disability related to post-traumatic headache was high with an average NRS ranging from 5.5 at baseline to 5.7 at 60-month follow-up [14]. Moderate-to-severe TBI makes post-traumatic headache worse compared to mild TBI [23].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it was reported that disability related to post-traumatic headache was high with an average NRS ranging from 5.5 at baseline to 5.7 at 60-month follow-up [14]. Moderate-to-severe TBI makes post-traumatic headache worse compared to mild TBI [23].…”
Section: Discussionmentioning
confidence: 99%
“…4,5,11,14 This number will vary significantly depending on the original questions posed to the patients, but usually is a problem with questionnairebased diagnostic queries. 4,5,11,14 This number will vary significantly depending on the original questions posed to the patients, but usually is a problem with questionnairebased diagnostic queries.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike traumatic tissue injury, which resolves with time, the natural history of PTH shows itself to be remarkably persistent. [3][4][5] In addition, although many existing headache medications used for primary headache disorders are prescribed to those with PTH, many have noted that few people respond well to them, and no medications have adequately established efficacy in prospective studies. 6 Furthermore, symptom profiles of patients with PTH are heterogeneous, and the profiles of multiple primary headache conditions appear to predominate concurrently in many of these individuals 7,8 and thus do not sit well or are not classifiable within existing primary diagnostic criteria.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations